Analisis Hubungan Variabel Pemilihan Moda Transportasi dengan Pilihan Moda Transportasi Pelajar SMAN 7 Bandung Tahun Ajaran 2022/2023 - Fauzan Mochammad Fidhiaz; Dadan Mukhsin (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract.Transportation is a necessity for many elements of society, including students. In reaching school, students can use various types of transportation modes such as private, public, and online transportation. Having previously been disrupted by the COVID-19 pandemic, the 2022/2023 academic year will be the year when teaching and learning activities begin to be carried out normally. Although things are slowly returning to normal, COVID-19 has affected many things, including choosing a mode of transportation. The return to normal educational activities created the need for transportation to school to re-emerge. Therefore, the authors are interested in conducting research that aims to identify preferences for mode selection between private, online, and public transportation among students in the 2022/2023 school year. SMAN 7 Bandung was chosen as a case study in this research. The methodology used in this research is revealed preference approach with cross tab analysis method. Based on data collection, it was found that private transportation was the mode of transportation most used by SMAN 7 Bandung students to go to school after the COVID-19 pandemic. Based on the variables observed, there are several variables that have a significant relationship with the type of transportation mode chosen. Overall, the variables that have a significant relationship with the choice of transportation mode for students at SMAN 7 Bandung are Pocket Money (X4), Method of Departure (X6), and Cost (X9). Abstrak.Transportasi merupakan kebutuhan untuk banyak elemen masyarakat, termasuk pada pelajar. Dalam mencapai sekolah, para pelajar dapat menggunakan berbagai jenis moda transportasi seperti transportasi pribadi, umum, maupun online. Setelah sebelumnya sempat terganggu oleh pandemi COVID-19, tahun ajaran 2022/2023 menjadi tahun dimana kegiatan belajar mengajar mulai dilakukan secara normal. Walau perlahan kembali berjalan normal, COVID-19 sudah mempengaruhi banyak hal, termasuk dalam memilih moda transportasi. Kembali berjalan normal kegiatan pendidikan menciptakan kebutuhan akan transportasi menuju sekolah kembali muncul. Maka dari itu, penulis tertarik untuk melakukan penelitian yang bertujuan untuk mengidentifikasi preferensi pemilihan moda antara transportasi pribadi, online, dan umum pada pelajar tahun ajaran 2022/2023. SMAN 7 Bandung dipilih sebagai studi kasus dalam penelitian. Metodologi yang digunakan dalam penelitian ini adalah pendekatan revealed preference dengan metode analisis tabulasi silang (cross tab). Berdasarkan pengumpulan data, didapat bahwa transportasi pribadi menjadi moda transportasi yang paling banyak digunakan oleh pelajar SMAN 7 Bandung untuk berangkat ke sekolah pasca pandemi COVID-19. Berdasarkan variabel yang diamati, terdapat beberapa variabel yang memiliki hubungan signifikan dengan jenis moda transportasi yang dipilih. Secara keseluruhan, variabel yang memiliki hubungan signifikan dengan pemilihan moda transportasi pelajar SMAN 7 Bandung adalah Uang Saku (X4), Cara Berangkat (X6), dan Biaya (X9).